2018
DOI: 10.1080/15548627.2018.1489946
|View full text |Cite
|
Sign up to set email alerts
|

Rocaglamide enhances NK cell-mediated killing of non-small cell lung cancer cells by inhibiting autophagy

Abstract: Targeting macroautophagy/autophagy is a novel strategy in cancer immunotherapy. In the present study, we showed that the natural product rocaglamide (RocA) enhanced natural killer (NK) cell-mediated lysis of non-small cell lung cancer (NSCLC) cells in vitro and tumor regression in vivo. Moreover, this effect was not related to the NK cell recognition of target cells or expressions of death receptors. Instead, RocA inhibited autophagy and restored the level of NK cell-derived GZMB (granzyme B) in NSCLC cells, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…Previous studies also reported sensitizing tumors to NK cell activity by targeting alternate signaling pathways in tumors, including inhibition of BRAF (V600E) (310), STAT3 inhibition (311), and modulation of cancer cell autophagy (312,313).…”
Section: Upregulation Of Nk Cell Ligandsmentioning
confidence: 98%
“…Previous studies also reported sensitizing tumors to NK cell activity by targeting alternate signaling pathways in tumors, including inhibition of BRAF (V600E) (310), STAT3 inhibition (311), and modulation of cancer cell autophagy (312,313).…”
Section: Upregulation Of Nk Cell Ligandsmentioning
confidence: 98%
“…In normal cells, autophagy has been shown to suppress malignant transformation. However, once malignant transformation has occurred, autophagy can promote tumor progression and resistance to therapy [4]. Therefore, autophagy is considered a promising therapeutic candidate for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In supporting this, activation of autophagy has been shown to mediate the peritumoral monocyte‐induced cancer progression of human hepatocellular carcinoma, as well as the astrocyte‐induced promotion of breast cancer metastasis to the brain [5,10]. Of particular interest, inhibition of autophagy has been shown to mediate the natural killer cell‐induced killing of non‐small‐cell lung cancer cells [4]. Therefore, targeting autophagy is suggested as a promising strategy for cancer therapy [4,5].…”
mentioning
confidence: 99%
“…In addition, a growing body of evidence shows that Chinese herbs and its effective ingredients can exert tumor suppressive effects through multiple ways, including induction of apoptosis, anti-metastasis and anti-angiogenesis, proliferation inhibition, suppression of cancer stem-like cells, induction of autophagy, etc. [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%